Particularities of Variation of the Dental Wear in Subjects with Cardiovascular Diseases Compared to Subjects without Systemic Diseases - Mihart, Mirela; Mercuț, Veronica; Popescu, Sanda Mihaela; Vlăduțu, Diana-Elena; Pîrgaru, Anca Mihaela; Scrieciu, Monica (Current health sciences journal, 2024)
analysis of dental wear variation in subjects with cardiovascular diseases (CVDs), compared to subjects without systemic diseases (SDs). the study included 84 hospitalized subjects with CVDs and 84 without SDs subjects, who presented to the Dental Emergency Department of the Emergency Clinical Hospital in Drobeta Turnu Severin. The subjects' data were processed descriptively, by analysis of variance and simple and multiple linear regression. Subjects with CVDs had a mean age±SD:69.49±10.09, and subjects without SDs had a mean age±SD:58.98±5.61. In subjects with CVDs, out of 504 sextants, 360 (174 maxillary and 186 mandibular) were included in the dental wear assessment, and in subjects without SDs, out of 504 sextants, 480 (242 maxillary and 238 mandibular) were evaluated. The number of remaining teeth (NRT) ranged between 2 and 25 (mean±SD 15.54±5.43) for subjects with CVDs, and between 16 and 27 (mean±SD 22.64±2.47) for subjects without SDs. Analysis of variance of the wear score values assigned to the indicated the highest value F (2, 249) =71.09768707, with F (2, 249)> F crit. (3.032064916) for mandibular sextants in the CVDs subjects. Regression models adjusted independently with gender, age, residence and NRT, revealed a coefficient with values between 11.97%-28.72% for CVDs subjects and between 11.90%-20.88% for subjects without SDs. dental wear varied for both categories of subjects in the mandibular arch, compared to the maxillary arch, in their frontal area, compared to the lateral areas, depending on age, residence and NRT.